Construction of the Tycho reference catalogue - Kuzmin, Andrei; Bastian, Ulrich; Röser, Siegfried (Astronomy & astrophysics. Supplement series, 1999)
The Tycho Reference Catalogue (TRC) project, as proposed in 1992 by the present authors, aimed to extend the Hipparcos reference system to fainter magnitudes. To assure rigidity of the reference system realization, the project relied on the Tycho Cataloguethat provides highly-accurate positions of more than one million stars on the Hipparcos system. To maintain the precision of the reference system over longer periods of time, high-precision proper motions must be derived from Tycho and earlier ground-based measurements, most notably the century-old Astrographic Catalogue(AC). The recently published first version of the Tycho Reference Catalogue provides highly-accurate positions and proper motions for 990 182 stars of the Tycho Catalogue. It realizes the ICRS/Hipparcos system in the optical domain with a median accuracy of 45 mas at epoch J2000.0. The realization is based on stars of median magnitude $B_{T}=11.25$ mag, providing an average of 24 reference stars per square degree. The median accuracy of the TRC proper motions, estimated from external comparisons as 2.4 mas/yr, ensures a reference system realization with an accuracy better than 100 mas over the time span of a few decades. Highly-accurate astrometry combined with homogeneous two-colour Tycho photometry makes TRC an ideal choice for a wide range of astronomical applications. The present paper covers the major steps of the TRC construction, including the Astrographic Cataloguereduction onto the Hipparcos system, identification of the Tycho Catalogue stars in the AC, derivation of proper motions, a posteriori systematic corrections of the proper motions to account for residual AC systematic errors, and the TRC quality assessment. The relation of the TRC with the recently published ACT catalogue is outlined. A future version of the TRC, to be based on the new Tycho data processing and a global block adjustment of the Astrographic Catalogue, is briefly discussed.
Gesehen am 18.02.2018
Gesehen am 16.02.2018